Efektivitas Pendayagunaan Zakat Produktif Pada Badan Amil Zakat Nasional (BAZNAS) Di Kabupaten Bone - Kadriani, Nur Annisa; Amin, Muhammadiyah; Alimuddin (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2025)
This research focuses on the effectiveness of utilizing productive zakat at the National Zakat Amil Agency (BAZNAS) in Bone Regency. What the author explores is the form and influence of the use of productive zakat on mustahik. This research is a field research, with the sources of this research being observation, interviews and documentation. The results of this research show that through the productive use of zakat, the funds given to mustahik are used as business capital. There are several forms of utilizing productive zakat, namely traditional productive zakat and creative productive zakat. The influence obtained by mustahik who are channeled with business capital assistance is quite influential in developing mustahik businesses, although productive zakat funds can only help in the business sector, they can influence all aspects of social life, or the welfare of mustahik lives. Regarding effectiveness, the utilization of productive zakat is quite effective in helping develop mustahik businesses to alleviate poverty, however the implementation of monitoring is less than optimal due to a lack of monitoring staff. There is a need to increase socialization of zakat utilization programs, so that the programs at the National Zakat Amil Agency in Bone district are widely known to the public.K eywords: Productive Zakat, BAZNAS, Empowerment, effectiveness.